POLÍTICA CULTURAL EM TEMPO DE CRISE: o Ministério da Cultura no Governo Temer - Alexandre Barbalho (Revista de Políticas Públicas, 2018)
This article is part of the broader eRort to analyze the crisis of Brazilian cultural policy that has been underway since the Ana de Hollanda administration in the Ministry of Culture. In the proposed clipping for this work, one investigates the unfolding of this phenomenon in the Temer government, in the administration of the minister Sergio Sá Leitão. As a theoretical-methodological contribution, the concepts of field and state in Pierre Bourdieu are used. As a conclusion, it’s visible the conformation of cultural policy to the policy of neoliberal reform underway in the current government.